Ordinary spaces and affections in the city: filmic heterotopia at Avenida Brasília Formosa (Comunicação & Inovação, 2016)
In this article, we analyze the movie AvenidaBrasília Formosa, discussing how the mise-en-scènearticulates elements when reinstating the cityof Recife, Brazil. Therefore, we will focus in theshapes, emphasizing the creation of spatialitiesand temporalities. The movie focus on the BrasíliaTeimosa favela, one of the redevelopment marksin Brazil in recent years, creating onthe scene aspace tightly bound to the experiences and affectionsof the filmed subjects. This spatiality, gainingdepth in everyday corporeity, composes an"other space", or heterotopia, as Michel Foucaultconceptualizes.
Keywords: Ordinary life. Everyday life. Heterotopia.